Association of endothelial nitric oxide synthase gene polymorphisms with coronary artery disease: an updated meta-analysis and systematic review. - Himanshu Rai; Farah Parveen; Sudeep Kumar; Aditya Kapoor; Nakul Sinha (PLoS ONE)
Several association studies of endothelial nitric oxide synthase (NOS3) gene polymorphisms with respect to coronary artery disease (CAD) have been published in the past two decades. However, their association with the disease, especially among different ethnic subgroups, still remains controversial. This prompted us to conduct a systematic review and an updated structured meta-analysis, which is the largest so far (89 articles, 132 separate studies, and a sample size of 69,235), examining association of three polymorphic forms of the NOS3 gene (i.e. Glu298Asp, T786-C and 27 bp VNTR b/a) with CAD. In a subgroup analysis, we tested their association separately among published studies originating predominantly from European, Middle Eastern, Asian, Asian-Indian and African ancestries. The pooled analysis confirmed the association of all the three selected SNP with CAD in three different genetic models transcending all ancestries worldwide. The Glu298Asp polymorphism showed strongest association (OR range = 1.28-1.52, and P<0.00001 for all comparisons), followed by T786-C (OR range = 1.34-1.42, and P<0.00001 for all comparisons) and 4b/a, (OR range = 1.19-1.41, and P ≤ 0.002 for all comparisons) in our pooled analysis. Subgroup analysis revealed that Glu298Asp (OR range = 1.54-1.87, and P<0.004 for all comparisons) and 4b/a (OR range = 1.71-3.02, and P<0.00001 for all comparisons) have highest degree of association amongst the Middle Easterners. On the other hand, T786-C and its minor allele seem to carry a highest risk for CAD among subjects of Asian ancestry (OR range = 1.61-1.90, and P ≤ 0.01 for all comparisons).